Upconversion nanoparticle as a theranostic agent for tumor imaging and therapy - Wenkai Fang; Yanchun Wei (Journal of Innovative Optical Health Sciences, 2016)
Upconversion nanoparticles (UCNPs) as a promising material are widely studied due to their unique optical properties. The material can be excited by long wavelength light and emit visible wavelength light through multiphoton absorption. This property makes the particles highly attractive candidates for bioimaging and therapy application. This review aims at summarizing the synthesis and modification of UCNPs, especially the applications of UCNPs as a theranostic agent for tumor imaging and therapy. The biocompatibility and toxicity of UCNPs are also further discussed. Finally, we discuss the challenges and opportunities in the development of UCNP-based nanoplatforms for tumor imaging and therapy.